Cuidados de enfermería en un recién nacido prematuro con dificultad respiratoria por abstinencia neonatal - Moreira Mendoza, Vanessa Paola (2024)
Neonatal abstinence, also known as neonatal abstinence syndrome (NAS), is a condition that affects newborns exposed to addictive substances in utero. Premature newborns with NAS face additional challenges due to their incomplete development and immaturity of their physiological systems. This condition manifests itself with a variety of symptoms that can include irritability, tremors, feeding problems, difficulty sleeping, and, in severe cases, seizures. Respiratory distress is a common complication in these newborns due to lung immaturity and metabolic overload caused by withdrawal. In this case study, the 32-week premature newborn patient with a birth weight of 1600 grams is presented. Respiratory distress and neonatal withdrawal symptoms due to the mother's history of drug use are addressed. The newborn was born with upper extremity cyanosis, an elevated respiratory rate, and seizures, indicating a significant challenge to his cardiovascular and respiratory system. The evaluation includes vital signs and laboratory results that highlight the severity of your condition. Nursing plays an essential role in constant monitoring, administering oxygen, observing seizures, and collaborating with the medical team to ensure comprehensive care in this critical period of your neonatal life.